How concerning is Lucifer? Insights from an experimental study of public responses to heat event naming in England and Italy - Barbara Summers; Andrea Taylor; Pietro Bellomo; Suraje Dessai (Meteorological Applications)
Abstract Summer 2023 saw record high temperatures across several European countries with these heat events being unofficially dubbed Cerberus and Charon. This has led to discussion about whether naming severe heat events is an effective way to convey the risks posed. In online experiments with regionally representative sample of members of the public in England and Italy, we assessed the effect of giving a heat event a mythological, non‐mythological or no name on anticipated severity, concern, trust/confidence and behavioural intention. We find that while naming alone does not have a strong effect on anticipated response to severe heat events in either country, going against the established trend of using mythological names in Italy could diminish concern.